The Association between Blood-Based Global DNA Methylation and Venous Thromboembolism - Wang, Xiao; Memon, Ashfaque A.; Palmér, Karolina; Svensson, Peter J.; Sundquist, Jan; Sundquist, Kristina (Seminars in Thrombosis and Hemostasis, 2020)
Alterations in DNA methylation patterns have been associated with many diseases. However, the role of DNA methylation in venous thromboembolism (VTE) is not well established. The aim of this study was to investigate a possible association between global DNA methylation and VTE. The study participants consisted of 168 individuals including 74 patients with primary VTE from the Malmö Thrombophilia Study (MATS) and 94 healthy controls. Among 74 primary VTE patients, 37 suffered VTE recurrence during the follow-up period; 37 nonrecurrent VTE patients were included for comparison. Blood-based global DNA methylation was assessed by an enzyme-linked immunosorbent assay. Global DNA methylation was significantly higher in primary VTE patients compared with the healthy controls (median: 0.17 vs. 0.08%; p < 0.001). After stratification of data from primary VTE patients according to sex, the association between higher global DNA methylation and shorter recurrence-free survival time was of borderline statistical significance in males (β = –0.2; p = 0.052) but not in females (β = 0.02; p = 0.90). Our results show that global DNA methylation is associated with primary VTE and that higher levels of global DNA methylation may be associated with early VTE recurrence in males but not in females. Further investigation on the role of DNA methylation as a diagnostic or preventive biomarker in VTE is warranted.
Keywords: venous thromboembolism; DNA methylation; recurrent venous thromboembolism